STUDY OF GUAR GUM, ALUM, AND WATER ADDITION ON PHYSICAL CHARACTERISTICS OF EXTRUDED WET CORN NOODLE - Aminullah, Aminullah; Muhandri, Tjahja (Jurnal Pertanian, 2019)
Corn noodle was a form of food diversification, especially food that usually used wheat flour as its raw material. The objective of this research was to study the effects of guar gum, alum, and water addition on physical properties of extruded wet corn noodle. It was made by mixing wet and dried flours, steaming dough, pressing it using an paste extruder, and steaming the noodles. The alum, guar gum, and water concentrations were 0% and 0.01%; 0%, 1%, and 2%; and 60%, 70%, and 80%, respectively. The physical analysis of wet corn noodle were color, elongation, hardness, adhesiveness, and cooking loss analysis. The analysis showed that wet corn noodles have a reddish yellow color with °Hue of 83.21° - 86.42°. The statistical analysis showed that the higher the guar gum concentration led to the lower the hardness and cooking loss of wet corn noodle, while the greater the elongation. Alum addition increased the hardness and elongation of wet corn noodles, while it decreased the adhesiveness.